Phenylbutazone concentrations in synovial fluid following administration via intravenous regional limb perfusion in the forelimbs of six adult horses - O’Brien, Molly; Mochel, Jonathan P.; Kersh, Kevin; Wang, Chong; Troy, Jarrod (Frontiers in Veterinary Science, 2023)
Background: Pain management is critical to equine welfare with non-steroidal anti-inflammatory drugs (NSAID) commonly used in horses. However, systemic NSAID use is limited by harmful gastrointestinal and renal side effects. Intravenous regional limb perfusion (IVRLP) is a technique used in horses that produces high, local antibiotic concentrations while limiting systemic circulation. NSAID-IVRLP would be a novel method of local pain management while limiting systemic NSAID side effects. To date, NSAID-IVRLP administration has not been reported in horses. This study aimed to identify the pharmacokinetics and local complications associated with using the NSAID phenylbutazone (PBZ) for IVRLP in 6 standing adult horses. Methods: PBZ-IVRLP, at a dose of 2.2 mg/kg PBZ, was performed in a randomly assigned forelimb cephalic vein in 6 standing, healthy adult horses. A placebo-IVRLP was performed in the contralateral forelimb for comparison. Systemic serum and radiocarpal joint synovial fluid PBZ concentrations were identified at various timepoints (before IVRLP T-0h, just after tourniquet removal T-0.5h, 1.5, 3, 5, 12, 16, and 24 hours post IVRLP) for non-compartmental pharmacokinetic analysis and concentration over time curves. Local complications associated with PBZ-IVRP were evaluated for up to 7 days following PBZ-IVRLP using physical and ultrasonographic assessment. On day 7 horses were humanely euthanized with histology performed on both forelimbs at PBZ-IVRLP and placebo-IVRLP administration sites. Results: Non-compartmental pharmacokinetics for PBZ, and its major metabolite oxyphenbutazone (OBZ), were determined for serum and synovial fluid. Synovial PBZ concentrations (mean + SD; 1.9 + 2.1 ug/mL) were significantly lower (P=0.03; CI,0.46-7.36) than serum PBZ concentrations (5.8 + 5.1 ug/mL) at any time point. Physical and ultrasonographic measurements were not significantly different between PBZ- and placebo-IVRLP forelimbs. The most common histologic findings included focal deep dermal/subcutaneous hemorrhage and edema. Two horses showed perivasculitis and 1 horse showed a resolving thrombus in the cephalic vein of the PBZ-IVRLP limb. This horse also had severe perivasculitis and fibrinosuppurative dermatitis/panniculitis in the placebo-IVRLP limb. Conclusions: PBZ-IVRLP pharmacokinetics at a 2.2 mg/kg dose showed no benefit compared to systemic PBZ administration in standing adult horses. Local complications associated with PBZ-IVRLP were similar to placebo-IVRLP on physical and ultrasonographic evaluation.